Effect of Boron Trioxide Enriched Fluxes on the Microstructure and Mechanical Properties in Submerged Arc Welded Mild Steel Plates - Gupta, Pushpendra; Roy, Joydeep; Saha, S. C. (Advanced Aspects of Engineering Research Vol. 1, 2021)
Among the several arc welding methods, the submerged arc welding is the preferred method for welding thick sections in the industry because of its several advantages which include high production rates, good weld quality, ease of automation and minimum operator skill requirement. This paper represents a study on the effect of B2O3 additions in fluxes on the microstructure and mechanical properties of the weld metal formed during Submerged Arc Welding of Mild Steel plates. Five fluxes with about 2.5, 5, 7.5, 10 and 12.5% B2O3 were used with a low carbon electrode. Welding process parameters were kept constant for all the conditions. The microstructure of weld metal for each flux consisted mainly of acicular ferrite, polygonal ferrite, grain boundary ferrites and equiaxed pearlite. It was noted that Vicker’s hardness value was a function of boron content and showed a mixed trend. Impact Energy and Tensile Strength were increased with the increase in boron content in welds this can be attributed to relation with the higher acicular ferrite percentage. However, an optimum level of toughness and tensile strength was available with 7.5% and 5% of B2O3 respectively. A qualitative comparison has also been made with fresh flux through full metallography and mechanically.